Hegemoni Hollywood Pada Film American Sniper - Melis Tanaka; J. A. Wempi (Program Studi Ilmu Komunikasi FISIP Universitas Syiah Kuala, 2019)
Most movies shown in Indonesian cinemas are Hollywood movies. From existing genres, war movies tend to be used by Hollywood to spread their hegemonic practices. American Sniper, which was released in 2014, is one of the examples. The heroic scene acted by the main lead persuades the audience that America has a hero involved in Navy SEALs. This study was qualitative research using a critical paradigm. Hollywood’s hegemony in the film American Sniper (2014) could be understood by elaborating the three dimensions of Critical Discourse Analysis by Norman Fairclough, along with the theory of hegemony by Antonio Gramsci. The result of the research shows that in microanalysis, there are universal and idealist elements such as patriotism, nationalism, and loyalty. Meso analysis found that PT. Omega Film is a registered distributor of Film Censorship Institute (LSF) as part of the Political Society, according to Gramsci, which plays a significant role in the distribution of Hollywood films in Indonesia. Based on the macro analysis, the American Sniper (2014) film is one of the hegemonic practices of Hollywood in the era of neo-conservative that contains American centric.